Editorial (Latin-American Journal of Computing, 2021)
During the years of existence of LAJC Journal, we have been able to evidence the technological development of the society that is moving towards modernity through the increasingly common inclusion of ICT "Information and communication technologies" in the different human activities, be it the implementation of ICT in the fields of education, health, commerce, etc.The New Technologies have marked, in recent years, an acceleration of their pace and the scope of their generalization. Currently, we see the growing importance of information in all types of activities, and therefore of ICT, which are affirmed in developed countries and also in emerging ones, as tools that offer an opportunity for the development of society.We know that companies, whether small, medium or large, are recognized as an essential element of the development of a country and, due to their contribution and redistribution of incomes in favor of employment, economic growth and, consequently, the fight against poverty and social inequalities. These organizations need to adapt to technological evolution, in which, information can be both a threat and an opportunity. A company that manages this situation well can benefit from the flexibility and capacity that allow it to adapt to its market and be competitive.In this context, this issue of LAJC Journal is special, since it officially opens up publications that deal with the study of technology and its relationship with organizational development through the analysis of contemporary paradigms and the generation of knowledge in these environments.I cordially invite you to take advantage of reading this issue, which includes outstanding research articles related to relevant topics such as the impact of teleworking during the COVID-19 pandemic period; proposals to improve the complementarity between engineering and social sciences in the higher education system in Ecuador. It also presents a manuscript about the use of neural networks and genetic algorithms, and other about academic performance prediction models, technological innovation for business performance, digital transformation.Likewise, our LAJC Journal extends a cordial invitation to explore the development of society linked to the evolution of ICT, through the eight volumes published in these 7 years.Finally, my sincere thanks to the LAJC team, that we can continue with the commitment to share scientific production in service of the development of society.